Effects of low-intensity blood flow restriction training on myocardial injury indices, antioxidant and anti-apoptotic capacity in rats - ShangGuan, Yuwen; Huang, Kunyi; Zhu, Zining; Yuan, Yuan; Song, Yawei; Wang, Hao; Chen, Liang; Yu, Shiqi; Zheng, Guangzhi; Liang, Qi (Frontiers in Physiology, 2025)
ObjectiveThis study aims to investigate the effects of low-intensity blood flow restriction training on myocardial tissue in rats. By measuring the levels of myocardial injury biomarkers in serum and the expression of anti-apoptotic and antioxidant proteins in myocardial tissue, the study preliminarily explores the underlying mechanisms.MethodsMale 3-month-old Sprague-Dawley rats were randomly divided into the following groups: control group (CON), low-intensity training group (LIRT), high-intensity training group (HIRT), and low-intensity blood flow restriction training group (LIBFR), with 6 rats in each group. Body weight, maximum voluntary carrying capacity, myocardial morphology, myocardial injury biomarkers, and the expression levels of Bcl-2, Bax, Nrf2, and Keap1 proteins in myocardial tissue were evaluated.Results(1)cTn1 Detection: The HIRT group showed a significant increase in cTn1 levels (P < 0.01), while the LIBFR group had a lower cTn1 level compared to the HIRT group (P < 0.05). (2)Nrf2 and Keap1 Results: Compared to the CON group, the LIBFR group showed an increase in Nrf2 (P < 0.05), and a significant increase in Keap1 (P < 0.01). (3)Bcl-2 and Bax Results: Compared to the CON group, Bcl-2 levels were significantly elevated in the HIRT group (P < 0.01) and increased in the LIBFR group (P < 0.05), while Bax expression was significantly reduced in the LIBFR group (P < 0.05). Regarding the Bcl-2/Bax ratio, the LIRT, HIRT, and LIBFR groups exhibited significantly higher values compared to the CON group (P < 0.01). Furthermore, the HIRT and LIBFR groups showed significantly higher Bcl-2/Bax ratios than the LIRT group (P < 0.01).ConclusionLow-intensity blood flow restriction training can effectively reduce cTn1 in rat serum, decrease cardiomyocyte apoptosis, and improve antioxidant capacity, which has a certain protective effect on the myocardium.